2021
DOI: 10.1542/peds.2020-024182
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Bariatric Surgery in Older Versus Younger Adolescents

Abstract: OBJECTIVES: In this report, we compare weight loss, comorbidity resolution, nutritional abnormalities, and quality of life between younger and older adolescents after metabolic and bariatric surgery. METHODS: From March 2007 to December 2011, 242 adolescents (≤19 years of age) who underwent bariatric surgery at 5 clinical centers in the United States were enrolled in the prospective, multicenter, long-term outcome study Teen–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 66 publications
1
14
0
2
Order By: Relevance
“…Other co‐obesity‐related comorbidities such as hypertension, dyslipidaemia and proteinuria were significantly reduced in the Teen‐LABS group 158 . Multiple other studies have supported the role of surgery in reducing obesity‐related comorbidities 159–162 …”
Section: Definitionmentioning
confidence: 81%
“…Other co‐obesity‐related comorbidities such as hypertension, dyslipidaemia and proteinuria were significantly reduced in the Teen‐LABS group 158 . Multiple other studies have supported the role of surgery in reducing obesity‐related comorbidities 159–162 …”
Section: Definitionmentioning
confidence: 81%
“…Initial results after bariatric surgery in morbidly obese adolescents with metabolic comorbidities suggested that these procedures improved an impaired glucose metabolism and other cardiometabolic comorbidities even in this age group and could even be more effective than in adults [ 67 , 68 , 69 ]. Moreover, there are only few differences in the outcome of bariatric surgery (RYGB and SG) between younger and older adolescents, suggesting that younger adolescents with severe obesity should not be denied consideration for surgical therapy [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Ogle, Dewberry, Jenkins et al examined 5-year outcomes of patients who underwent bariatric surgery from two cohorts: younger (age 13–15 years) and older (age 16–19 years). They found few differences in outcome in these two cohorts, to include percentage weight loss after 5 years, improvement or resolution of hypertension, type 2 diabetes, dyslipidemia, nutritional abnormalities and quality of life [29 ▪ ].…”
Section: Metabolic and Bariatric Surgerymentioning
confidence: 99%